New and poorly known Acrolepiinae from the Palaearctic, Afrotropical, Neotropical and Oriental regions (Lepidoptera: Glyphipterigidae) - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Six new species are described: Digitivalva kenyacola, Acrolepiopsis falcata, Acrolepiopsis lativalvata, Acrolepiopsis juratae, Acrolepiopsis fibigeri, Acrolepia peruana. The female genitalia of Acrolepiopsis jaspidata (Meyrick, 1919) are described for the first time. New country records are established for four species: Acrolepia dioscoreivora Gibeaux, 1989, Acrolepiopsis nagaimo Yasuda, 2000, Acrolepiopsis brevipenella Moriuti, 1972, Acrolepiopsis persimilis Moriuti, 1974. The first specimens of Acrolepiopsis halosticta (Meyrick, 1914) apart from the type series were found. Acrolepiopsis persimilis Moriuti, 1974, hitherto regarded as a synonym of Acrolepiopsis suzukiella (Matsumura, 1931), is re-established as a valid species. Keywords Palaearctic, Afrotropical region, Neotropical region, Oriental region, Lepidoptera, Glyphipterigidae. Nomenclatural Acts falcata Gaedike, 2016 (Acrolepiopsis), spec. nov. fibigeri Gaedike, 2016 (Acrolepiopsis), spec. nov. juratae Gaedike, 2016 (Acrolepiopsis), spec. nov. lativalvata Gaedike, 2016 (Acrolepiopsis), spec. nov. persimilis Moriuti, 1974 (Acrolepiopsis), stat. rev. valid, not a synonym of Acrolepiopsis suzukiella (Matsumura, 1931) peruana Gaedike, 2016 (Acrolepiopsis), spec. nov. kenyacola Gaedike, 2016 (Digitivalva), spec. nov.